Peremajaan Permukiman Dengan Pendekatan Pembangunan Yang Bertumpu Pada Masyarakat Sebagai Alternatif Penanganan Permukiman Kumuh - Dicky Handrianto (Journal of Regional and City Planning, 1996)
In dealing with the problem of slum area, people often become the victim of the way the problem is handled. Encountered with difficulties and the desire to deal with the problems quickly, often result in temporary cure which is harmful to people and often ended with eviction.Excluding people in the decision making process and put them only as object of the action resulted in failures which always accompany the handling of slum area. Unreachable sustainability and social conflict which obstruct the handling process are sonic of the failures in dealing with the slum area problems. Slum area renewal with community based development approach is an alternative which is trying to answer and eliminate the weaknesses of the conventional handling process.